IPTEK BAGI MASYARAKAT: PERANCANGAN DAN IMPLEMENTASI SOFTWARE LAPORAN KEUANGAN UNTUK KELOMPOK PETERNAK BEBEK DI DESA KOBONDUREN KABUPATEN BLITAR - Nurika Restuningdiah Restuningdiah; Cipto Wardoyo (Jurnal Akuntansi Aktual, 2015)
Problems faced by groups of farmers duck is lack of knowledge of accounting, and there is no software for the preparation of financial statements for the farmer duck, To overcome the problems, then the solution is development software for financial reporting. The Development method of the software using System Development Life Cycle (SDLC)Keywords: duck farm,financial reporting software for duck farmer